PERKEMBANGAN BANK UMUM SYARIAH PASCA COVID-19 - Evi Maulida Yanti; Fatmayanti Fatmayanti; Fakhrurrazi Fakhrurrazi (Jurnal Real Riset, 2022)
The corona virus has a fairly broad impact on the activities carried out by the community, one of which has an impact on economic activity in banking financial institutions, both in conventional and Islamic banks. The type of research used is field research. This research is descriptive qualitative which means it describes the research subject. The data analysis technique used in this study, the author uses a qualitative descriptive analysis. The growth of Islamic Commercial Banks during the COVID-19 pandemic in 2020 decreased and began to recover in 2021. The non-performing financing component experienced a reduced risk of problems until 2021, due to more selective financing distribution. Likewise, the DPK indicator which includes savings, current accounts and deposits experienced a setback in 2020 and returned to white in 2021. Thus, it can be concluded that Islamic Commercial Banks are also faltering with the presence of the Corona outbreak that hit the world, after the Covid-19 development of Commercial Banks Sharia is slowly recovering.Keywords : Corona, Islamic Commercial Banks, Economy